The anti-inflammatory cytokine IL-22 exhibited a proinflammatory effect in the ovary aiding with the parturition of ovoviviparous black rockfish (Sebastes schlegelii) - Yan, Shaojing; Lyu, Likang; Wang, Xiaojie; Wen, Haishen; Li, Yun; Li, Jianshuang; Yao, Yijia; Zuo, Chenpeng; Xie, Songyang; Wang, Zhijun; Qi, Xin (Frontiers in Marine Science, 2022)
As a unique type of immunological process, pregnancy and subsequent parturition are associated with a series of inflammatory events. As an anti-inflammatory cytokine, IL-22 has been proven to participate in the parturition process in mammals. However, less is known about ovoviviparous teleosts. To investigate the role of IL-22 in fish parturition, black rockfish, an ovoviviparous teleost, was used. This fish is unique in that it provides over 60% nutrition supply for over 50 thousand embryos at the same time though a placenta-like structure during pregnancy while delivering all fries in two hours. Sequence alignment, phylogenetic tree analysis and homology modeling were performed on IL-22 and its receptor. In situ hybridization results showed that both il22 and il22ra1 were localized in the perinatal follicle layer and embryonic envelope. The il22 expression level was significantly increased during parturition compared to before and after parturition (P<0.05). To further understand the mechanism of IL-22 in parturition, rIL-22 was obtained. The downstream variation genes in primary cultured ovarian cells in the perinatal period were analyzed according to the transcriptomic results. A total of 168 differentially expressed genes (DEGs) were identified in the rIL-22 group compared with the PBS control group (padj < 0.05 and |log2FoldChange| ≥ 1). Of those, 134 DEGs were identified in the LPS and rIL-22 treatment groups, including chemokine, cytokine, and PG synthesis. 34 DEGs were mainly identified in immune-related pathways and reorganization of the cytoskeleton responded only to rIL-22 stimulation but not LPS. KEGG pathways mainly included immune response, PG synthesis, cell death and angiogenesis (pvalue < 0.05). Taken together, our results indicated that IL-22 plays an important role in the parturition of black rockfish by upregulating PG synthesis and increasing chemokine, proinflammatory factor, as well as PG synthetase levels.